If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16y + -12x = -100 Reorder the terms: -12x + 16y = -100 Solving -12x + 16y = -100 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16y' to each side of the equation. -12x + 16y + -16y = -100 + -16y Combine like terms: 16y + -16y = 0 -12x + 0 = -100 + -16y -12x = -100 + -16y Divide each side by '-12'. x = 8.333333333 + 1.333333333y Simplifying x = 8.333333333 + 1.333333333y
| 2X-14=-x+1 | | X-10y+z=39 | | x^5-6x^4+11x^3-6x^2=O | | (3x-5)+3x=11 | | 3x-5+3x=11 | | 3x+2y+5z=-12 | | x/100=11/100 | | 32(1-x)-7(x+4)=-44 | | Y+y=14 | | 0.32(1-x)-0.7(x+4)=-0.44 | | -3x=x-16 | | 8x=9x+7 | | 7x-30=-44 | | 84t/-8= | | 16t+68t+8= | | x^2+4y^2-z^2+100=96 | | k/-2-11=5 | | 2y-17=y+4 | | k-2-11=5 | | X^2-29x-754=0 | | 6+y-3=11 | | y=x^7+5x^6 | | 4x^2+4y^2+12x-4y=-1 | | k^4-2k^2+k^2-12=0 | | x^2+2-63= | | 3x+2y+3z=100 | | x=2y-3a | | 3x-17=20x-36+2x | | 3h=-t+3z | | x^(5/3)−5x^(2/3)=0 | | 7x-15=3x+11 | | 6e(5x+2)=18 |